Perancangan UIUX Aplikasi Mobile Edukasi Budaya Betawi dengan Design Thinking dan Usability Testing secara Kualitatif - Pramudiawardani, Shelly; Tegar Asayahanda Firdaus; Perdi Satriama; F Rachmat Kautsar (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
The digitalization of cultural preservation through education is crucial in the digital era. The Betawi Cultural Community, Sanggar Bale Bambu in Depok, West Java, faces challenges in introducing Betawi culture to the public, particularly in the documentation and management of cultural services. Although many studies on cultural digitalization exist, few educational applications directly collaborate with cultural communities and support cultural services. This study aims to design the User Interface (UI) and User Experience (UX) of a mobile application as a learning medium for Betawi culture and cultural services, beginning with user needs identification to minimize development errors. The method used is Design Thinking, which emphasizes empathetic understanding of user needs and produces innovative solutions. The research process includes problem formulation, empathy, ideation, responsive prototyping using Figma, and qualitative Usability Testing. The result is an application Prototype with six main educational features: pencak silat, ondel-ondel, Betawi music, Betawi accessories, lenong, and palang pintu. Testing showed that the application is easy to use, informative, and effective as a digital medium for introducing Betawi culture. Further research can continue with in-depth quantitative Testing, back-end integration, and broader user Testing for additional validation.